Neurochemical and behavioral processes in gerontogenesis in conditions of experimental hyperglycemia. - O. Rodynskyi; K. Basysta; L. Guz (Medičnì Perspektivi)
Many researchers are increasingly interested in the relation between diabetes and diabetic encephalopathy. At the moment, there are various experiments where this issue is considered. But despite prolonged studying, it is impossible to investigate this problem to the end. Cognitive deficit in hyperglycemia is also connected with aging. In the aging processes as in hyperglycemia the same pathogenetic factors play a role in the aging of the brain. It is also necessary to deeply analyze the neurochemical processes occurring in the brain in diabetes mellitus. The high incidence of complications is caused by tissue metabolism impairment in hyperglycemia. The study of neurochemical bases of brain activity is one of the leading and promising directions in the modern neuropathology. Scientists of different countries are searching for neurospecific damage markers of the brain substance in hyperglycemia.